Digital Image Processing in Clinical Decision Support System for the Cervix Differential Diagnosis - A. A. Motyko; N. A. Obukhova (Известия высших учебных заведений России: Радиоэлектроника)
New methods of image processing and analysis for clinical decision support system of differential diagnosis of conditions of the cervix tissues are reviewed. The proposed method of colposcopic images processing allows to synthesize a special image that simulates the application to visualize vessels and to provide better analysis of vascular structures by the physician.